Synergy of Pedagogical Content Knowledge, Digital Literacy, and Instructional Design Skills in Preparing Quality Elementary Teachers for Impactful Learning - Sundahry; Syahrial; Yantoro; Destrinelli (Postgraduate, University of Mataram, 2026)
This study examines how Pedagogical Content Knowledge (PCK), digital literacy, and instructional design skills synergistically influence perceived impactful learning among elementary teacher education students. A sequential explanatory mixed-methods design was employed: quantitative data from 222 students via surveys, followed by qualitative data from 15 students through focus group interviews. Quantitative results show PCK and instructional design skills collectively explain 70% of variance in impactful learning, with balanced and strong effects, while digital literacy functions as a supporting enabler rather than primary determinant. Qualitative findings identify six facilitating factors, eight barriers, and seven moderators that contextualize competency integration patterns. The study proposes three conceptual frameworks Synergistic Competency Framework, Grade Responsive Pedagogy Framework, and Pedagogy Primacy Framework integrated within the Subject-Specific Deep Learning Pedagogy (SSDLP) model, which positions PCK as the foundational layer for technology-enhanced instruction. Conclusions emphasize that impactful learning emerges when pedagogical foundations precede technological integration, with field experience and intrinsic motivation as critical catalysts. Teacher education programs should prioritize systematic PCK development, positioning digital literacy as complementary infrastructure.